Relations of weight status and physical fitness of children in Slovenia - Matejek Črtomir; Planinšec Jurij; Fošnarič Samo; Pišot Rado (Sciendo, 2014)
Aim: The main aim of the research was to find out whether there are any differences in physical fitness between non-overweight, overweight and obese children.